Effect of Sample Size on Sound Velocity Measurement Error by Pulse Transmission Method - LI Jiahui; CHEN Dehua; HE Xiao; ZHANG Xiumei (Cejing jishu)
The acoustic velocity measurement of core samples can provide crucial reservoir geological information, with practical application value in reservoir evaluation and geological model construction. The pulsed transmission method is a commonly used method for measuring sound velocity, but it often requires a sample size much larger than the wavelength (about 10 times larger). In instances where specific conditions require the measurement of sample sound velocity at the logging main frequency range of 8～20kHz, it is necessary for the sample being measured to have a length of several meters. Not only the sample preparation is difficult, but also the problem of large attenuation of acoustic signal. There are few published reports of targeted quantitative studies on whether or to what extent the size of the specimen can be reduced. This study integrates numerical simulations with experimental measurements to systematically and quantitatively explore the impact of the ratio between the length and diameter of cylindrical samples and the wavelength on the precision of the pulse transmission method for sound velocity assessment. The researches indicate that for accurate measurement of sound velocity using the pulse transmission method, it is advisable to have the sample length along the propagation direction be at least four times the wavelength of the sound wave, and the transverse size to be at least twice the wavelength. The research results have overcome the constraint associated with the conventional pulse transmission technique, which necessitates the sample size to be significantly larger than the wavelength. These results offer theoretical underpinning for enhancing the measurement approach of sound velocity and elevating the precision of measurements.